RANCANG BANGUN ALAT PEMECAH KACA, WATER MIST, DAN PINTU OTOMATIS SAAT TERJADI KEBAKARAN PADA BUS BERBASIS ARDUINO - faalih, dhiya ulhaq (Journal of Infrastructural in Civil Engineering, 2024)
Fire is a disaster caused by several factors including human factors, technical factors and natural factors. Bus fires often occur due to short circuits caused by fuel line leakage problems. Fires that occur on buses often claim lives, due to a lack of knowledge about the use of safety equipment that is facilitated on each bus. In the safety of bus travel, an APAR (light fire extinguisher) has also been provided, and a glass breaker hammer that can be used if there is a threat of fire hazard or other accidents on the bus. In addition, there is also an emergency door as an option for the evacuation process in the event of an accident. Not everyone can use the safety devices on the bus. Because there was panic which resulted in not having time to read directions or instructions during an evacuation in an urgent or emergency situation.Research and Development (R&D) is a method in which research is used to produce a particular product and test the effectiveness of the method. Research and Development aims to produce a design for a glass breaker, water mist and automatic door in the event of a fire on an Arduino-based bus and test the work of the tool.This research was made and tested by simulating a fire using a DHT 11 temperature sensor and a fire sensor as input. The tools in this study can break plain glass with a thickness of 2mm, 4mm, 5mm, 6mm. with a distance of 5cm. extinguish the fire using a hose sprayer, and open the door automatically if the fire sensor reads that there is a flame.